Breastfeeding Support Rooms and Their Contribution to Sustainable Development Goals: A Qualitative Study - De Souza, Carolina Belomo; Venancio, Sonia Isoyama; da Silva, Regina Paula Guimarães Vieira Cavalcante (Frontiers in Public Health, 2021)
Objectives: Breastfeeding support rooms are low-cost interventions that may prolong breastfeeding and improve work performance. Thus, we sought to understand the experiences and perceptions of working women who use breastfeeding support rooms and the potential contribution to sustainable development goals. Methods: Descriptive and exploratory research was conducted through convenience sampling of women working in companies with breastfeeding support rooms in the state of Paraná, Brazil. A semi-structured questionnaire was applied through interviews and online self-completion. Results: Fifty-three women between 28 and 41 years old participated in the study. In addition, 88.7% had graduated from college, and 96% were married. From the women's experiences and perceptions, we identified that breastfeeding support rooms contribute to prolonged breastfeeding, improve physical and emotional well-being, allow women to exercise their professional activities comfortably, contribute to women's professional appreciation for the excellent relationship between employees and employers. Conclusion: In this novel study, we demonstrate how, from a female point of view, breastfeeding support rooms can contribute to 8 of the 17 sustainable development goals and should therefore be encouraged and promoted.